Nanoscale Study of the Polar and Electronic Properties of a Molecular Erbium(III) Complex Observed via Scanning Probe Microscopy - Ivanov, Maxim; Grempka, Arkadiusz; Buryakov, Arseniy; Nikitin, Timur; Justino, Licinia L. G.; FAUSTO, RUI; Vilarinho, Paula M.; Paixao, Jose A. (MDPI, 2023)
We successfully synthesized millimeter-sized single crystals of the molecular erbium(III) complex Er(acac)(3)(cphen), where acac = acetylacetonate and cphen = 5-chloro-1,10-phenanthroline. The novelty of this work stems from the exhaustive examination of the polar and electronic properties of the obtained samples at the macro-, micro-, and nanoscale levels. The single crystal X-ray diffraction method demonstrates the monoclinic (noncentrosymmetric space group P2(1)) crystallographic structure of the synthesized samples and scanning electron microscopy exhibits the terrace-ledge morphology of the surface in erbium(III) crystals. By using the piezoelectric force microscopy mode, the origin of the polar properties and the hyperpolarizability in the synthesized samples were assigned to the internal domain structure framed by the characteristic terrace-ledge topography. The direct piezoelectric coefficient (similar to d33) was found to be intensely dependent on the local area and was measured in the range of 4-8 pm/V. A nanoscale study using the kelvin probe force and capacitance force (dC/dz) microscopy modes exposed the effect of the Er ions clustering in the erbium(III) complex. The PFM method applied solely to the Er ion revealed the corresponding direct piezoelectric coefficient (similar to d33) of about 4 pm/V. Given the maximum piezoelectric coefficient in the erbium(III) complex at 8 pm/V, we highlight the significant importance of the spatial coordination between the lanthanide ion and the ligands. The polar coordination between the lanthanide ion and the nitrogen and oxygen atoms was also corroborated by Raman spectroscopy supported by the density functional theory calculations. The obtained results can be of paramount importance for the application of molecular erbium(III) complex crystals in low-magnitude magnetic or electric field devices, which would reduce the energy consumption and speed up the processing switching in nonvolatile memory devices.
Keywords: Erbium(III); Integrated Magnetoelectric Molecular System; Piezoresponse Force Microscopy (PFM); Kelvin Probe Force Microscopy (KPFM)